Comprehensive study of cost, seismic & wind impacts on circular water tanks with varying cylindrical height-to-diameter ratio - Saxena S.; Pathak K.K. (My University, 2025)
This study had systematically assessed the cost and material efficiency of circular water tanks with varying capacities, closely examining the influence of cylindrical height-to-diameter (H/D) ratios within the range of 0.2 to 2.0. The investigation has delved comprehensively into the effects of wind and seismic forces, accounting for both tank-filled and empty conditions across the entire spectrum of H/D ratios. The analysis has specifically focused on water storage capacities of 600, 700, 800, 900, 1000, 1100, and 1200 kiloliters. Employing an in-house Software Program developed for the Design of Elevated Circular Water Tanks and adhering to the guidelines of IS 3370:2021, the study has conducted a thorough parameter comparison to reveal substantial cost savings achievable through strategic H/D ratio selection. Particularly noteworthy is the revelation that the H/D ratio optimizing cost aligns with the configuration that experiences minimal wind and seismic forces. Informed parameter have choices emerged as a driving force behind considerable reductions in material consumption, underscoring the software program's efficacy as a pivotal tool for designing elevated water tanks, particularly in scenarios where conventional analysis and design software lack accessibility. © 2024, National Institute of Science Communication and Policy Research. All rights reserved.